Insights into brown spider and loxoscelism - M H Appel; R Bertoni da Silveira; W Gremski; S S Veiga (Invertebrate Survival Journal, 2005)
Loxosceles is a genus of cosmopolitan spiders comprising several species, and popularly known as brown spiders or brown recluses. Brown spider bites can cause dermonecrotic lesions and systemic reactions known as loxoscelism. Systemic effects are less common but may be severe or even fatal in some patients. Systemic manifestations include intravascular hemolysis, disseminated intravascular coagulation and acute renal failure. A rapid diagnosis and an understanding of the venom’s molecular activity are crucial for satisfactory treatment. Mechanisms by which venoms exert their deleterious effects are under investigation, and searches are underway for diagnostic envenomation assays. Molecular biology is being used to produce quantities of several of the most important venom molecules and has contributed to the study and understanding of their mechanisms of action.